Active materials: minimal models of cognition?. (December 2020) - McGivern, Patrick
Work on minimal cognition raises a variety of questions concerning the boundaries of cognition. Many discussions of minimal cognition assume that the domain of minimal cognition is a subset of the domain of the living. In this article, I consider whether non-living 'active materials' ought to be included as instances of minimal cognition. I argue that seeing such cases as 'minimal models' of (minimal) cognition requires recognising them as members of a class of systems sharing the same basic features and exhibiting the same general patterns of behaviour. Minimal cognition in this sense is a very inclusive concept: rather than specifying some threshold level of cognition or a type of cognition found only in very simple systems, it is a concept of cognition associated with very minimal criteria that pick out only the most essential requirements for a system to exhibit cognitive behaviour.